MEMAHAMI PENGARUH JIWA DAN NILAI KEWIRAUSAHAAN TERHADAP KEMANDIRIAN USAHA DI KOTA PALU: STRATEGI UNTUK PEMBERDAYAAN EKONOMI LOKAL - Rizka Fardha (Lafadz Jaya Publisher, 2023)
This research aims to investigate the influence of entrepreneurial spirit, entrepreneurial values, and entrepreneurial behavior on the self-reliance of small business entrepreneurs in Palu City. The main issues identified in this research include limited access to financing, difficulties in marketing local products, bureaucratic barriers, and a lack of capacity in small and medium-sized enterprises in the city. This qualitative research method involved 125 respondents who are small business entrepreneurs registered with the Department of Cooperatives and SMEs in Palu City. Data were collected through questionnaires and analyzed using the Structural Equation Modeling (SEM) technique. The results of this research indicate that entrepreneurial behavior has a positive and significant influence on self-reliance, while entrepreneurial spirit and entrepreneurial values do not have a significant influence on self-reliance. Therefore, emphasis should be placed on the development of entrepreneurial behavior, with a focus on aspects such as self-confidence, wise decision-making, and active efforts in business development. In conclusion, self-reliance can also be influenced by external factors such as government policies and access to financial resources.